Semi-surgical percutaneous dilatational tracheostomy vs. conventional percutaneous dilatational tracheostomy: A prospective randomized trial - Novin Nikbakhsh; Fatemeh Amri; Mahmood Monadi; Parviz Amri; Ali Bijani (Babol University of Medical Sciences, 2021)
Background: Percutaneous dilatational tracheostomy (PDT) is a common surgical procedure in the ICU. The present study was conducted to compare semi-surgical percutaneous dilatational tracheostomy (SSPDT) with conventional percutaneous dilatational tracheostomy (CPDT). Methods: The present randomized clinical trial was conducted on 160 patients hospitalized in the medical intensive care units (ICUs) with an indication for tracheostomy and were systematically divided into two equal groups of 80. In the CPDT group, after a small incision, a 16-gauge needle was blindly inserted into the trachea and the guidewire was placed inside the lumen. A stoma was created by passing a single dilator over the guidewire. In the SSPDT group, a transverse incision (2 cm) was made 1 cm below the cricoid, and the tracheal ring was then fully reached by releasing the subcutaneous tissues using the index figure, and PDT was then performed. The two groups were compared in terms of their tracheostomy complications (including bleeding, pneumothorax, stoma infection and accidental decannulation) and duration of the procedure. Results: The two groups were homogeneous in terms of age, gender, mean APACHE score (P>0.05). There were no significant differences between the two groups in terms of the mean time from tracheal intubation to tracheostomy (P=0.869). The duration of the procedure was 5.16±1.72 minutes in the SSPDT group and 6.42±1.71 in the CPDT group (P<0.001). The complication rate was 7(8.75%) in the SSPDT group and 16(20%) in the CPDT group (P=0.043). Conclusion: SSPDT is safer and has fewer complications than CPDT in ICU patients.